The prominence of the title on the exhibit label (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
Word and art are what mostly differentiates us from animals. Not only because of their great power to convey a message, but also because of their essential repercussions in today's western culture. With a conceptual approach, the aim is to elucidate between a theoretical and a practical approach, with the protagonism falling on what, until now, has been considered in many cases, at most, as an accessory: the title and, consequently, the exhibit label in art. The first as a creative material that the artist can use for his work; and the second as a paradigmatic tool for providing a simultaneous and parallel hermeneutic contextualisation to the artistic exhibition. The autonomy between the two, also with respect to the factuality of the work, can present challenges of great magnitude, in order to incorporate other public profiles, capturing the interest of new spectators who are not necessarily ‘connoisseurs’ of art.
Keywords: Title; Exhibit Label; Hermeneutics; Mediation; Context